ITGBL1 modulates integrin activity to promote cartilage formation and protect against arthritis - Song, Eun Kyung; Jeon, Jimin; Jang, Dong Gil; Kim, Ha Eun; Sim, Hyo Jung; Kwon, Keun Yeong; Medina-Ruiz, Sofia; Jang, Hyun Jun; Lee, Ah Reum; Rho, Jun Gi; Lee, Hyun Shik; Kim, Seok Jung; et al. (Science Translational Medicine, 2018)
Developing and mature chondrocytes constantly interact with and remodel the surrounding extracellular matrix (ECM). Recent research indicates that integrin-ECM interaction is differentially regulated during cartilage formation (chondrogenesis). Integrin signaling is also a key source of the catabolic reactions responsible for joint destruction in both rheumatoid arthritis and osteoarthritis. However, we do not understand how chondrocytes dynamically regulate integrin signaling in such an ECM-rich environment. Here, we found that developing chondrocytes express integrin-β-like 1 (Itgbl1) at specific stages, inhibiting integrin signaling and promoting chondrogenesis. Unlike cytosolic integrin inhibitors, ITGBL1 is secreted and physically interacts with integrins to down-regulate activity. We observed that Itgbl1 expression was strongly reduced in the damaged articular cartilage of patients with osteoarthritis (OA). Ectopic expression of Itgbl1 protected joint cartilage against OA development in the destabilization of the medial meniscus-induced OA mouse model. Our results reveal ITGBL1 signaling as an underlying mechanism of protection against destructive cartilage disorders and suggest the potential therapeutic utility of targeting ITGBL1 to modulate integrin signaling in human disease.
Keywords: Aged; Animals; Cartilage, Articular; Cell Differentiation; Cell Line, Tumor; Chondrocytes; Chondrogenesis; Disease Models, Animal; Embryo, Nonmammalian; Extracellular Matrix; Face; Gene Expression Regulation; Humans; Integrin beta1; Joints; Mesenchymal Stem Cells; Mice; Middle Aged; Osteoarthritis; Xenopus